2017
DOI: 10.1126/sciadv.1701533
|View full text |Cite
|
Sign up to set email alerts
|

A variational approach to probing extreme events in turbulent dynamical systems

Abstract: A variational framework for the analysis and data-driven prediction of extreme events is developed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 43 publications
4
95
1
Order By: Relevance
“…the rescaled approximating SDE (8) can be written more compactly as (a) The control term modifies the potential V in the original SDE (2) to the effective potential (9). The term α|x − x a | 2 /2 increases the potential gap around the desirable state x a , deepening the potential well.…”
Section: Approximating Sdementioning
confidence: 99%
“…the rescaled approximating SDE (8) can be written more compactly as (a) The control term modifies the potential V in the original SDE (2) to the effective potential (9). The term α|x − x a | 2 /2 increases the potential gap around the desirable state x a , deepening the potential well.…”
Section: Approximating Sdementioning
confidence: 99%
“…We also stress that the method proposed here can be generalized to the full two-dimensional setting, as well as other relevant physical systems where an understanding of extreme events is important [21,22] but made challenging by the complexity of the models involved combined with the stochasticity of their evolution and the uncertainty of their parameters [21,[23][24][25][26]. In this sense our approach adds to the several methods developed specifically to explain the mechanism and likelihood of rare but important events [27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…(6) We note that this simplified control is a scalar multiple of the external forcing f . The corresponding probability distributions of the energy dissipation D are nearly identical whether we use the full control (5) or its simplified form (6). Figure 5 shows the closeup view of an extreme event at Re = 40; it compares the uncontrolled and controlled system trajectories starting from the same initial condition.…”
Section: Navier-stokesmentioning
confidence: 96%
“…During these bursts, the energy dissipation D increases to several standard deviations above its expected value (see figure 2(a)). Using a variational method, Farazmand and Sapsis [6] showed that these bursts are preceded by a nonlinear energy transfer from the Fourier modeû (1,0) to the modeû(0, 4). Shortly before an extreme energy dissipation event is observed, most of the energy content of the Fourier modê u(1, 0) is transferred to the Fourier modeû(0, 4).…”
Section: Uncontrolled Systemmentioning
confidence: 99%